2012
DOI: 10.1007/s12639-012-0214-0
|View full text |Cite
|
Sign up to set email alerts
|

Thiosulphate: cyanide sulphur transferase activity in some species of helminth parasites

Abstract: Investigation on the characteristic pattern of enzymes in various organisms may be of particular importance, as this type of information can help to understand certain physiological and biochemical processes in living organisms. Thiosulfate: cyanide sulfurtransferase (rhodanese) is a ubiquitous multifunctional enzyme, which its major function is generally believed to be in cyanide detoxification. The present study was conducted to determine the activity of this enzyme in some parasitic helminths including, ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Baghshani et al [33] reported that at least some rhodanese activity was present in seven investigated parasitic helminths, including Haemonchus longistipes, although its activity was much lower than the values previously reported for some tissues of their vertebrate hosts. The role of rhodanese in parasitic helminths is fascinating given its wide distribution.…”
Section: -mentioning
confidence: 71%
“…Baghshani et al [33] reported that at least some rhodanese activity was present in seven investigated parasitic helminths, including Haemonchus longistipes, although its activity was much lower than the values previously reported for some tissues of their vertebrate hosts. The role of rhodanese in parasitic helminths is fascinating given its wide distribution.…”
Section: -mentioning
confidence: 71%
“…Baghshani et al reported that at least some rhodanese activity was present in all the seven investigated parasitic helminths including Haemonchus longistipes, although its activity was much lower than the values previously reported for some tissues of their vertebrate hosts [33]. The role of rhodanese in parasitic helminth is fascinating given it's widely distribution.…”
Section: Introductionmentioning
confidence: 89%
“…Baghshani et al reported that at least some rhodanese activity was present in seven investigated parasitic helminths, including Haemonchus longistipes, although its activity was much lower than the values previously reported for some tissues of their vertebrate hosts [33]. The role of rhodanese in parasitic helminths is fascinating given its wide distribution.…”
Section: Introductionmentioning
confidence: 93%